Using Q‐methodology to determine students' perceptions of interprofessional anatomy education. Issue 5 (18th November 2021) - Mackinnon, Chelsea; Akhtar‐Danesh, Noori; Palombella, Andrew; Wainman, Bruce
Abstract: Interprofessional education (IPE) prepares healthcare students for collaboration in their future careers. The purpose of this study was to determine which aspects of the IPE Program in Anatomy at McMaster University contributed to the development of healthcare student's interprofessional skills. Q‐methodology was used to identify the students' common viewpoints of the IPE experience. A total of 26/28 (93%) of students in the course from the medical, nursing, midwifery, physician assistant, occupational therapy, and physiotherapy programs participated in this study. Students were asked to sort a Q‐sample of 43 statements about the IPE dissection course derived from previous qualitative studies of the program. Using the centroid factor extraction and varimax rotation, three salient factors (groups) emerged, namely: (1) Anatomy IPE Enthusiasts, (2) Practical IPE Advocates, and (3) Skeptical IPE Anatomists. The Anatomy IPE Enthusiasts believed that students from different disciplines brought unique anatomical knowledge and each group member guided others through difficult material. The Practical IPE Advocates expressed that they would be stronger advocates for interprofessional teams in the future because of the course. The Skeptical IPE Anatomists strongly disagreed that learning with students from different disciplines helped them gain an understanding of their roles in the context of other healthcare professionals and felt that there was little benefit from the IPE program compared to other non‐interprofessional programs. These findings about student attitudes are critical to drive an evidence‐based evolution of the IPE dissection course, since students' perceptions can have a profound influence on interprofessional collaboration in the workplace.